Rap1 Is Essential for B-Cell Locomotion, Germinal Center Formation and Normal B-1a Cell Population - Ishihara, Sayaka; Sato, Tsuyoshi; Sugioka, Risa; Miwa, Ryota; Saito, Haruka; Sato, Ryota; Fukuyama, Hidehiro; Nakajima, Akihiko; Sawai, Satoshi; Kotani, Ai; Katagiri, Koko (Frontiers in Immunology, 2021)
Integrin regulation by Rap1 is indispensable for lymphocyte recirculation. In mice having B-cell-specific Rap1a/b double knockouts (DKO), the number of B cells in lymph nodes decreased to approximately 4% of that of control mice, and B cells were present in the spleen and blood. Upon the immunization with NP-CGG, DKO mice demonstrated the defective GC formation in the spleen, and the reduced NP-specific antibody production. In vitro, Rap1 deficiency impaired the movement of activated B cells along the gradients of chemoattractants known to be critical for their localization in the follicles. Furthermore, B-1a cells were almost completely absent in the peritoneal cavity, spleen and blood of adult DKO mice, and the number of B-cell progenitor/precursor (B-p) were reduced in neonatal and fetal livers. However, DKO B-ps normally proliferated, and differentiated into IgM+ cells in the presence of IL-7. CXCL12-dependent migration of B-ps on the VCAM-1 was severely impaired by Rap1 deficiency. Immunostaining study of fetal livers revealed defects in the co-localization of DKO B-ps and IL-7-producing stromal cells. This study proposes that the profound effects of Rap1-deficiency on humoral responses and B-1a cell generation may be due to or in part caused by impairments of the chemoattractant-dependent positioning and the contact with stromal cells.